"¿Para quién escribía Elena Fortún? Exilio y tensión autorial en Celia, institutriz en América (1944). (2nd April 2020) - García, María del Carmen Alfonso
ABSTRACT: In the 43rd issue of the Mexican journal Cuadernos Americanos (1949), Francisco Ayala published "Para quién escribimos nosotros", his milestone article on the reflection on the losses, alterations and uncertainties that would define the authorship of writers of the Spanish republican exile in itself and in its relationship with its possible readership. From the framework of Ayala's essay, this article studies Celia, institutriz en América, one of the novels written by Elena Fortún in her Buenos Aires exile, published in Madrid by Aguilar in 1944, to determine how the author responded to that general conflict. The aim is to focus on why, how and with what implications Elena Fortún enacts the tension between two forces: the fidelity to the literary project around the character of Celia, initiated in Spain before the Civil War and characterized by a renovating modernity, and the demands associated with a certain reception (resulting, in turn, from the symbolic and cultural pact that has redefined everything), which is not only that of the public, but also that of the official and ecclesiastical censorship instituted by the dictatorship as a guarantee of orthodoxy.